A review of mathematical modeling of fixed-bed columns for carbon dioxide adsorption - Shafeeyan, M.S.; Daud, W.M.A.W.; Shamiri, A. (Elsevier, 2013)
Carbon dioxide emissions must be stabilized to mitigate the unfettered release of greenhouse gases into the atmo-sphere. The removal of carbon dioxide from flue gases, an important first step in addressing the problem of CO2emissions, can be achieved through adsorption separation technologies. In most adsorption processes, the adsor-bent is in contact with fluid in a fixed bed. Fixed-bed column mathematical models are required to predict theperformance of the adsorptive separation of carbon dioxide for optimizing design and operating conditions. A comprehensive mathematical model consists of coupled partial differential equations distributed over time and spacethat describe material, energy, and the momentum balances together with transport rates and equilibrium equa-tions. Due to the complexities associated with the solution of a coupled stiff partial differential equation system, theuse of accurate and efficient simplified models is desirable to decrease the required computational time. The simpli-fied model is primarily established based on the description of mass transfer within adsorption systems. This paperpresents a review of efforts over the last three decades toward mathematical modeling of the fixed-bed adsorptionof carbon dioxide. The nature of various gas–solid equilibrium relationships as well as different descriptions of themass transfer mechanisms within the adsorbent particle are reviewed. In addition to mass transfer, other aspects ofadsorption in a fixed bed, such as heat and momentum transfer, are also studied. Both single- and multi-componentCO2adsorption systems are discussed in the review.